Association between vitamin D status and lipid profile in children and adolescents: a systematic review and meta-analysis. (June 2014) - Kelishadi, Roya; Farajzadegan, Ziba; Bahreynian, Maryam
Abstract This systematic review and meta-analysis was performed on the relationship of serum 25-hydroxy-vitamin D [25(OH)D] and lipid profile in the pediatric age group. Electronic search was conducted in international databases. Our search yielded to 3213 articles, with initial searching of title and abstracts, 3192 of them were excluded and 21 remained. A meta-analysis of 17 cross-sectional studies, including 25 394 subjects, was conducted according to Strobe guideline. We found an inverse weak significant association between 25(OH)D and triglycerides (r = −0.135, CI; −0.243, −0.025), total cholesterol (r = −0.086, CI; −0.0205, 0.035) and LDL-C (r = −0.025, CI; −0.22, 0.17), and direct association with HDL-C (r = 0.156, CI; −0.021, 0.324). In the pooled analysis, we used a random effects model as the heterogeneity between studies was significant (I2 = 97.04%, p < 0.001 for triglycerides; I2 = 96.09%, p < 0.001 for total cholesterol; I2 = 96.14%, p < 0.001 for LDL-C; I2 = 99%, p < 0.001 for HDL-C). This study indicates that higher serum 25(OH)D is related to a more favorable lipid profile in the pediatric age group.